Mechanisms And Problems of Financial Support for Innovative Entrepreneurship - Daniyarov Kuatbay Dauirxanovich (Academia Open, 2025)
Background (General): The rapid digitalization of economies has reshaped the entrepreneurial landscape, creating new opportunities for innovation while heightening the need for effective financial support systems. Background (Specific): Innovative entrepreneurship depends heavily on the availability and efficiency of direct and indirect financial mechanisms such as loans, grants, venture capital, and tax incentives. Knowledge Gap: Despite various financial instruments being established, little is known about how these mechanisms interact, overlap, and collectively influence innovation outcomes across different regions and sectors. Aim: This study examines the mechanisms and challenges of financial support for innovation-driven entrepreneurship, with the goal of developing a holistic understanding of their roles and effectiveness in the digital economy. Results: Findings indicate that while financial instruments drive innovation, their impact is constrained by limited accessibility, administrative complexity, and geographical disparities. Novelty: The research integrates multiple financial support mechanisms into a unified framework, highlighting how their interdependencies shape innovation outcomes. Implications: The study provides policy-oriented recommendations to enhance the inclusivity, efficiency, and regional balance of financial support systems, thereby strengthening innovation ecosystems and the sustainability of innovative enterprises.Highlight : The study emphasizes the role of direct and indirect financial support in fostering innovative entrepreneurship within the digital economy. It highlights barriers such as access to funding, administrative complexity, and regional disparities that limit effectiveness. The findings suggest improving financial literacy, policy adjustments, and diverse funding models to strengthen innovation systems. Keywords : Financial Support Mechanisms, Innovative Entrepreneurship, Digital Economy, Venture Capital, Grants